The application of in vitro fertilization techniques for the evaluation of ram fertility - PAPADOPOULOS (Σ. ΠΑΠΑΔΟΠΟΥΛΟΣ), S.; THEODOSIADOU (Α. ΘΕΟΔΟΣΙΑΔΟΥ), E.; KANTAS (Δ. ΚΑΝΤΑΣ), D.; VALASI (Ε. ΒΑΛΑΣΗ), E. (Journal of the Hellenic Veterinary Medical Society, 2018)
The prediction of field fertility of a given ram by using in vitro tests would be of great importance for the reproductive management in sheep flocks. There are many in vitro procedures available for evaluating semen quality and fertilizing ability, and the method chosen depends on the objective of evaluating the sperm and the available resources. The in vitro evaluation of semen fertilizing ability was firstly developed for the artificial insemination (AI) purposes and secondly for the application of in vitro fertilization (IVF) technique. The IVF techniques allow the assessment of fertility in terms of ability to penetrate and fertilize in vitro mature oocytes and ultimately to yield component embryos following IVF and culture. In this review are briefly presented in vitro studies performed in an attempt to establish an accurate laboratory test for the evaluation and, even more, the prediction of field fertility in sheep.